Classifying Search Queries To Digital Customer Purchasing Funnel Stages: A Machine Learning Approach - Engren, Veera (My University, 2019)
Understanding customer journeys is essential for marketers in order to guide consumers through the purchase funnel and respond more effectively to the consumers’ information needs in different stages of their buying journeys. Internet and social media have had a significant effect on consumer decision process and search engines have a central role in the consumer purchase journeys in the digital era. Also, year after year search engine marketing gains the biggest revenues in digital advertising. While targeting advertising according to the consumer purchase journey stages is considered important, manual efforts to classify all the keywords or search terms are not feasible. One search advertising account can include tens of thousands of keywords and consumer search queries are continuously evolving. This study presents a supervised machine learning approach to automatically classify consumer search queries into customer journey stages. Automated solutions are now a popular approach in the field of marketing, too, because of the vast amount of data available for decision-making. As machine learning becomes more and more usable and available for marketing purposes, it is important for practitioners to understand its possibilities and be aware of its limitations. For one of the cornerstones in supervised machine learning applications is the creation of training data, the study examined factors that affect the quality and validity of the training data and therefore the success of automatic classification. All in all, machine learning cannot provide valid results without representative training data. The research data consisted of 190 245 search queries gathered from the Google Ads account of a Finnish e-commerce company over a period of five years. Two different machine-learning algorithms, Random Forest and XGBoost, were applied and their results compared. The classifiers were able to find distinct classes and classify search queries accurately while no significant differences in the performance of the two classifiers were observed. The machine learning approach to large-scale automatic classification of search queries shows successful results and this method and these categories related to the purchase funnel can be used in analyzing customer behavior in different stages of the online purchase process or targeting advertising.

Kuluttajan ostopolun ymmärtäminen on oleellista, jotta markkinoijat pystyisivät paremmin tarjoamaan kuluttajalle relevanttia tietoa kussakin ostopolun vaiheessa, ja täten viemään kuluttajan koko ostofun-nelin (ns. ”ostosuppilon”) läpi. Internetillä ja sosiaalisella medialla on ollut suuri vaikutus kuluttajien ostokäyttäytymiseen. Digitalisaation myötä myös ostoprosessi on digitalisoitunut ja hakukoneita käytetään aktiivisesti päätöksenteossa. Hakukonemarkkinoinnilla onkin valta-asema digitaalisessa markkinoinnissa vuosi toisensa jälkeen. Hakukonemainonnan kohdentamista kuluttajan ostopolun mukaisesti pidetään tärkeänä, mutta kaikkien avainsanojen ja hakutermien luokittelu manuaalisesti ei ole järkevää. Mainostilit sisältävät runsain määrin avainsanoja, ja kuluttajien käyttämät hakutermit muuttuvat jatkuvasti ajan myötä. Tutkielma esittää automatisoidun keinon luokitella hakutermejä kuluttajan ostopolun vaiheisiin käyttäen ohjattua koneoppimista. Koska saatavilla olevan datan määrä on nykyisin valtava, ovat automaatioratkaisut suosittuja myös markkinoinnin alalla. Koneoppimisen käytettävyyden parantuessa tulisi markkinoinnin ammattilaistenkin ymmärtää sen tuomat mahdollisuudet sekä siihen liittyvät rajoitteet. Opetusdatan luominen on yksi ohjatun koneoppimisen kulmakivistä, ja siksi tutkielmassa tarkastellaan eri tekijöitä, jotka vaikuttavat opetusdatan laatuun ja sitä kautta automaattisen luokittelun onnistumiseen. Koneoppiminen ei pysty tuottamaan valideja tuloksia ilman edustavaa opetusdataa. Tutkimusaineisto koostui suomalaisen verkkokaupan Google Ads –tililtä haetuista hakutermeistä, joita oli yhteensä 190245 viiden vuoden ajalta. Datan luokitteluun testattiin kahta eri algoritmiä, Random Forestia ja XGBoostia, ja näiden tuloksia vertailtiin keskenään. Molemmat luokittelijat pystyivät erottamaan selkeitä luokkia ja luokittelemaan hakutermit hyvin tuloksin. Koneoppimisen soveltaminen laajamittaiseen automaattiseen hakutermien luokitteluun osoittautui toimivaksi. Tätä metodia ja ostofunneliin liittyviä kategorioita voidaan hyödyntää mainonnan kohdentamisessa sekä kuluttajakäyttäytymisen analysoimisessa ostoprosessin eri vaiheissa.
Keywords: Digital Marketing, Machine Learning, Search Engine Advertising, Purchase Funnel, Consumer Journey, Classifier, Algorithm, Random Forest, XGBoost, Google Ads